The Prevalence and Association of Stress with Sleep Quality during the COVID-19 Pandemic among Medical Students at Airlangga University - Adhitya Rizky Nugraha; Fidiana Fidiana; Khairina Khairina; Wardah Rahmatul Islamiyah (International Journal of Advanced Health Science and Technology, 2023)
The COVID-19 pandemic requires students to adapt to circumstances and cause various kinds of psychological problems during a pandemic outbreak. Some may experience stress, insomnia or hypersomnia. There are many factors causing poor sleep quality in students, including psychological problems such as stress which can worsen the quality of student’s sleep during the COVID-19 pandemic. This study aims to prove that there is a relationship between stress and the sleep quality of medical students at Airlangga University during the COVID-19 pandemic. This study is an observational analytic study using the cross-sectional design to assess the relationship between stress and sleep quality of respondents using the Pittsburgh Sleep Quality Index (PSQI) and Depression, Anxiety, Stress Scale - 42 (DASS-42) questionnaires. The research subjects were active pre-clinical students in the medical study program, Faculty of Medicine, Airlangga University, totaling 280 students who were divided into 3 batches, namely Class of 2019, Class of 2020, and Class of 2021. From the results of the study, it was found that 84.7% of students experienced poor sleep quality and a normal stress level of 55.5%. Sleep quality and stress levels are related to each other. This is proven by the Spearman rank analysis, which shows sleep quality is related to the stress level with a p-value = 0.000 and rho = 0.230. Based on these results, it was concluded that sleep quality and stress level have a positive correlation. The researcher expects that the institution will be able to use the study's findings as information about student stress levels and sleep quality in order to prevent stress and poor sleep or to implement health-related stress management programs for students.